Correlation between Sport Participation and Personal Development of Basketball Players (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Despite its popularity to enhance physical, emotional, and social skills, the existing studies mostly focus on athletes coming from well-resourced environments, leaving a gap in understanding how these benefits manifest in resource-limited settings. This study examined the relationship between sport participation and personal development of collegiate basketball players in the Mindanao State University (MSU). Using a descriptive-correlational approach, this research assessed sport participation using related variables, such as active years, training volumes, and competition levels. To measure personal development, life skill indicators, such as leadership, teamwork, and communication, were used. Data were collected from 48 basketball players across several MSU campuses using standardized questionnaires. Results of the study revealed a significant positive correlation between prolonged sport participation and improved personal development, particularly in teamwork, leadership, and problem-solving. The strongest correlation was found in the number of years of participation and training experience, with weaker associations for training frequencies and competition levels. These findings indicate that even in resource-limited environments, a consistent sport engagement could foster a meaningful personal growth. The study concludes that a structured sport program could contribute to a holistic development of athletes although additional resources and exposures to higher-level competitions could further enhance these benefits. Future research should investigate the impact of coaching quality and socio-cultural factors on personal development, particularly in under-resourced settings.